Horizontal Coffee Roaster Design with Temperature and Time Control - I Ketut Suherman; I Wayan Suwirya; Ni Wayan Merda Surya Dewi (Logic : Jurnal Rancang Bangun dan Teknologi, 2020)
National coffee have bean production reaches 600,000 tons for a year, only 20% that can be processed and marketed in to secondary products by roasted coffee, ground coffee, fast food coffee, and several types of secondary products derived from its derivatives and processing. The factors need to be considered when roasting, including temperature, time, expertise, and roasting techniques with a tool that is designed has dimension length 50 cm width 45 cm and height 110 cm. Coffee beans are roasted using a teflon griddle without a 25 cm cover diameter and Teflon griddle with a 16 cm cover diameter. The treatments studied were temperatures around 180 to 215oC with 12 minutes roasting time. The temperature treatment and roasting time affect the changes in mechanical physical properties of the coffee, namely a faster decrease in water content, increased fragility and accelerate changes in the color of darkness. Roaster machine based on microcontroller using gas fuel is made only 3 settings of coffee profile results, namely light, medium and dark with a light time of 12.8 minutes, medium 17 minutes and dark 25 minutes with a temperature setting of 245 degrees Celsius. The price of "roaster" is still very high because all the roasted tools in Indonesia are mostly imported so that they are not affordable by the household industry scale in relatively low income. So the authors make a prototype of a horizontal roaster model while still emphasizing traditional methods with temperature and time control. Temperature and time control here can be used to obtain the desired coffee profile qualit to reproduce creations roasted results. The dimensions are also small with a height of 60 cm, a width of 50 cm and a length of 60 cm and a frying pan diameter of 30 cm to hold 2 kg of coffee. This tool is designed with stainless steel and other parts used easily found on the market with the aim of facilitating maintenance and the main point is the application of appropriate technology with to increasing economic value. The results of testing the tool with a robusta coffee sample of 2 kilograms obtained the conclusion that the temperature and roasting time affect the profile of coffee produced and the roasting process can reduce the moisture content of coffee beans produced to improve quality of coffee profile.